Payday lending and the case of Proverbs 22:7: Wisdom for the borrower and warning to the lender. (February 2019) - Howell, Eric
The payday lending industry has become a wildly successful business model by taking advantage of the poor who turn to short-term, high-interest loans when faced with financial crises. Christian-oriented calls for personal responsibility and wiser financial decision-making appeal to Prov 22:7, "The borrower is the slave of the lender, " as warning to would-be borrowers. The proverb certainly signals caution to borrowers as it is commonly appropriated, but it also functions, in its context in Proverbs 22 and in concert with the whole of biblical economic justice, as a warning to would-be lenders not to take advantage of the vulnerable.